ENT 530 Social Media Portfolio: Lupus Rex Hobby / Amir Zakuan Saharuddin - Saharuddin, Amir Zakuan (2021)
Lupus Rex Hobby is a company that focuses on selling model kits or plastics model mainly from the famous animation series from Japan, Gundam. The term that is used internationally for our product is 'Gunpla' from the combination of word Gundam and plastic model. It is very popular among all level of age through the entire world including Malaysia. A great hobby that can bring out each creativity and brain process to build a Gunpla from head to toes. Our Company "Lupus Rex Hobby" comes with tagline "Providing Your Hobby Needs" is to provide our customers all the tools and model kits to fulfil their desirie. Trully a hobby-based business, from a fan to a fan of Gundam.